Assessment and Modeling of Adsorption Capacity of a Cationic Dye on the Natural Silica of El-Aouanajijel in North-Eastern Algeria. - Guerfi Samia; Filali Naima; Deghfel Nadir; Berredjem Yamina; Hattab Zhour (Annals of R.S.C.B., 2021)
The aim of this work is to study the adsorption of basic dye, methylene blue (MB), from an aqueous solution onto natural silica. The adsorption of MB by natural silica was carried out in static mode. Effects of parameters such as mass of adsorbant, initial dye concentration, stirring velocity, temperature, and pH on adsorption were investigated. In order to study the mechanism of the adsorption process, three kinetic models including pseudo-first order, pseudo-second order, and intra-particle diffusion were used. In addition, the linear Langmuir and Freundlich models were applied to describe equilibrium isotherms. The experimental results of adsorbent/adsorbate equilibrium show that the adsorption was well described by the kinetic model of pseudo-second order and by the Langmuir adsorption isotherm model. Optimal conditions for the adsorption of MB by natural silica were found to be: Va = 200 rpm, T = 25°C, and pH = 8.